The Risks and Factors of Influence on the Innovative and Investment Development of Agro-Industrial Production - Pavlova Halyna Ye.; Khalatur Oleksandr V. (Bìznes Inform, 2018)
The article is aimed at analyzing the risks and factors influencing the innovative and investment development of agro-industrial production. The current status of the agro-industrial production in Ukraine is analyzed. The carried out analysis has allowed to determine that the dangerous tendency consists in a high depreciation of the machine-technological park, and absence of financial means for implementing repair-restoration works only worsens its condition. According to the results of analytical researches and scientific generalizations, the genesis is revealed, the economic content of certain categories of the conceptual apparatus of the researched topic is determined, their competence and sphere of application are defined. The logical-structural scheme of the organizational-economic mechanism for innovative and investment development of enterprise is substantiated, its basic functions are characterized. It is determined that in practical activity of many agricultural enterprises the contemporary scientific-methodical basis of management of innovation-investment activity and of assessing its efficiency is not sufficiently used.